Poverty and income distribution - Krishnaswamy, K. S. (ed.) (Bombay, 1990)
While there has been, over the years, a perceptible increase in per capita income and expenditure and possibly some decline in the incidence of poverty in India, what still remains is massive and of a kind that is not remedied quickly or smoothly. Even with radical policies, the shifts in income and Occupational structures to make a serious dent on it will take more than the rest of this century. In the welter of recent exchanges between the government and the opposition as well as between planners and market advocates on the strategy of growth, these issues have been largely obfuscated. It is therefore more than ever necessary today to recognise the magnitude of the problem and the inadequacy of the measures adopted so far to deal with it. This selection of articles from Economic and Political Weekly on different aspects of poverty, unemployment and income distribution will, it is hoped, stimulate fresh discussion of the many methodological and policy questions that remain unresolved.
Keywords: Poverty